Literature Review: The Influence of Organizational Culture On Organizational Citizenship Behavior (OCB) With Employee Engagement As A Mediating Factor In Hospital - Saputro, Ivan Dwi; Kusumo, Mahendro Prasetyo (Journal of Business Management Education (JBME), 2024)
Understanding the influence of organizational culture on Organizational Citizenship Behavior (OCB) is essential for optimizing employee engagement and performance, particularly in the healthcare sector. This literature review investigates the relationship between organizational culture, OCB, and employee engagement, with a focus on medical personnel and nurses in hospital settings. Through a comprehensive analysis of existing literature, this study underscores the pivotal role of organizational culture in shaping OCB and highlights the mediating effect of employee engagement. Findings reveal that organizational culture significantly impacts OCB, with employee engagement serving as a crucial intermediary mechanism. The synthesis of previous research suggests that fostering a positive organizational culture is imperative for promoting OCB and enhancing employee engagement, ultimately benefiting both healthcare professionals and organizational outcomes. This review underscores the importance of strategic interventions aimed at leveraging organizational culture to optimize employee behaviors and organizational effectiveness in healthcare settings.